3d Modeling of the Thermal Phenomena During Laser Melting of Polymers - Siginer, D (American Society of Mechanical Engineers, 2018)
A comprehensive model of the selective laser sintering (SLS) process at the scale of the part is presented for application to polymeric powders. The powder bed is considered as a continuous medium with homogenized properties. A thermal model with detailed multiphysics coupling is presented. The model accounts for all elements of the thermal history : laser absorption, melting, coalescence, densification and volume shrinkage. For numerical resolution, a 3D in-house fortran code using FV method is developed. The proposed model is validated through the comparison of modeling data with experimental results available in the published literature. A parametric analysis about the thermal efficiency of the heating process against the laser energy input is proposed and the influence on the densification and thermal kinetics is discussed with regarding the evolution of the structure of the material. Copyright © 2018 ASME.